2000
DOI: 10.1073/pnas.97.23.12541
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric double-stranded RNA-specific adenosine deaminase ADAR1 proteins reveal functional selectivity of double-stranded RNA-binding domains from ADAR1 and protein kinase PKR

Abstract: The RNA-specific adenosine deaminase (ADAR1) and the RNA-dependent protein kinase (PKR) are both interferon-inducible doublestranded (ds) RNA-binding proteins. ADAR1, an RNA editing enzyme that converts adenosine to inosine, possesses three copies of a dsRNA-binding motif (dsRBM). PKR, a regulator of translation, has two copies of the highly conserved dsRBM motif. To assess the functional selectivity of the dsRBM motifs in ADAR1, we constructed and characterized chimeric proteins in which the dsRBMs of ADAR1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…50 With the exception of DIP1 dsRBD2, all dsRBDs that bind dsRNA are of type A. This has been demonstrated for Staufen, 44,51 TRBP, 24 XlRBPA, 52 PACT, 40 PKR, 49 ADAR, 53 RHA, 54 E3L, 55 RNase III, 56 and others with various intensities. In contrast, all dsRBDs type B that have been assayed show no RNA binding, 23 ,40,44,49,51,52 although they can cooperate with the other type for stronger RNA binding.…”
Section: Discussionmentioning
confidence: 95%
“…50 With the exception of DIP1 dsRBD2, all dsRBDs that bind dsRNA are of type A. This has been demonstrated for Staufen, 44,51 TRBP, 24 XlRBPA, 52 PACT, 40 PKR, 49 ADAR, 53 RHA, 54 E3L, 55 RNase III, 56 and others with various intensities. In contrast, all dsRBDs type B that have been assayed show no RNA binding, 23 ,40,44,49,51,52 although they can cooperate with the other type for stronger RNA binding.…”
Section: Discussionmentioning
confidence: 95%
“…Mutational analyses show that the dsRBM III motif of ADAR1 is essential for deaminase activity whereas RII is dispensable (217,237,240). Chimeric proteins in which the dsRBM of ADAR1 are replaced with those of PKR retain deaminase activity with synthetic dsRNA substrates but show dramatically reduced editing activity with natural RNA substrates (241). Furthermore, VAI and aptamer RNA antagonists of PKR significantly inhibit the deaminase activity of chimeric PKR-ADAR1 proteins but less so of wild-type ADAR1 (241).…”
Section: Rna-specific Adenosine Deaminase Adar1mentioning
confidence: 99%
“…Modulation of eIF-2␣ phosphorylation is the primary function of viral VAI RNA, at least in cell culture, because replacement of serine 51 by alanine not only eliminates the phosphorylation site on the eIF-2␣ substrate but also functionally complements the deletion of VA from the virus genome. Howerver, VAI RNA does antagonize ADAR1 (225,241) in addition to PKR (197,264). EBV-encoded EBER RNAs, which functionally can substitute for adenovirus VAI RNA in vivo, also inhibit PKR activation (68).…”
Section: Viral Antagonists Of Ifn-induced Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…If, for instance, the deaminase domains of ADAR1 and ADAR2 are exchanged, the resulting chimeric enzymes predominantly retain the substrate specificity determined by the deaminase domain (Wong et al 2001). On the other hand, the exchange of dsRBDs of ADAR1 with the ones from PKR leads to a dramatic reduction in substrate recognition of the chimeric protein (Liu et al 2000). Similarly, in Xenopus laevis oocytes it could be shown that Xenopus ADAR1 localizes to transcriptionally active lampbrush chromosomes and binds to the majority of nascent transcripts.…”
Section: Introductionmentioning
confidence: 99%